MENINGKATKAN HASIL BELAJAR PASING BAWAH DAN SERVIS ATAS DALAM BOLA VOLI MINI MELALUI PERMAINAN GALAGA KELAS IV SD NEGERI 1 KRIKIL KECAMATAN PAGERUYUNG KABUPATEN KENDAL TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
Mini volley ball games that have been implemented in the learning process at the elementary school level Penjasorkes not run effectively, service top and bottom passing students tend to be difficult to learn. This is due to the implementation process less than the maximum competency of students when students do service top and bottom passing. Than the problems faced galaga game whether modifications can improve the service learning outcomes service up and passing down game ball mini volleyball in grade fourth SD Negeri 1 Krikil, with the goal of improving learning outcomes service top and passing down the volleyball in SD Negeri 1 Krikil Kendal District 2012/2013. The method used in this study, the research methods class action. The learning cycle in the first cycle is 12 students with a percentage of 75% completeness, passing under 11 students with a 69% percent increase over the results services and passing down in the second cycle, while the number of 14 students for mastery percentage reached 87%.It can be concluded that the application of learning through play galaga modification can improve learning outcomes service upper and lower passing in grade fourth SD Negeri 1 Krikil country.